2018
DOI: 10.1037/neu0000433
|View full text |Cite
|
Sign up to set email alerts
|

Executive and social-cognitive determinants of environmental dependency syndrome in behavioral frontotemporal dementia.

Abstract: These findings reveal a complex interaction between executive dysfunction and mental attribution deficits influencing the prevalence of EDS in bvFTD. Further investigation is required to improve our understanding of the mechanisms underlying these behaviors. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Eslinger et al (2007), for example, reported that performance on the visual-verbal test was predictive of social dilemma judgments in patients with bvFTD. Previous studies have also found similar results using alternative tasks, including the Wisconsin card sorting test (Torralva et al, 2009, 2015; Flanagan et al, 2018).…”
Section: Discussionsupporting
confidence: 69%
“…Eslinger et al (2007), for example, reported that performance on the visual-verbal test was predictive of social dilemma judgments in patients with bvFTD. Previous studies have also found similar results using alternative tasks, including the Wisconsin card sorting test (Torralva et al, 2009, 2015; Flanagan et al, 2018).…”
Section: Discussionsupporting
confidence: 69%
“…Socially inappropriate behaviors like inappropriate familiarity or a lack of distance (e.g., staring at or touching the clinician, making inappropriate comments or jokes, being inappropriately jovial) during the anamnesis or during the cognitive assessment (e.g., walking out of the room, smiling, shrugging of shoulders) are often subtle signs of early behavioral disinhibition in bvFTD. Difficulties to inhibit irrelevant stimuli from the environment is often considered as a key feature of bvFTD and patients often struggle to focus on a task because of distractors [e.g., (67)], a symptom that has been linked to “environmental dependency” (68) and to increased stimulus-bound thought and behavior (69). Pathological gambling and personal neglect or reduced self-care (Diogenes syndrome) have been well-described (70, 71), as well as utilization or imitation behaviors (43, 72).…”
Section: The Clinical Diagnostic Criteria For Bvftdmentioning
confidence: 99%
“…Another commonly used test, the Trail-Making-Test part B (TMT-B) may even be more impaired in patients with AD compared to bvFTD (144) although bvFTD patients may be more insensitive to errors in this task (145). Environmental dependency symptoms such as imitation or utilization behavior have been described as more frequently observed in bvFTD than in AD (43, 72) but the variability of their assessment procedures and the probable multidimensionality of these symptoms (68) may have limited the investigations about their clinical relevancy and applicability. Even though saccade or anti-saccade abnormalities are sometimes reported as typical of bvFTD (46, 146), executive-related oculomotor function have been found to be impaired in AD as well (147), although they may be preserved in early disease stages (148).…”
Section: Cognitive Dysfunctions In Bvftdmentioning
confidence: 99%
“…The majority of ToM-studies in bvFTD did not control for cognitive abilities and there is evidence that ToM correlates with executive functioning in bvFTD (Baez et al, 2014; Gregory et al, 2002; Torralva et al, 2015). On the other hand, there is indirect evidence that ToM deficits can not be explained by global cognitive or executive dysfunction (Bertoux et al, 2016; Flanagan et al, 2018). A possible approach to reducing the impact of other cognitive processes on TOM function is the use of an implicit task.…”
Section: Introductionmentioning
confidence: 99%